Yazılı Basında Mülteci Haberleri Üzerine Karşılaştırmalı Bir İnceleme: The Guardian ve Hürriyet Örneği / A Comparative Study on Refugee News in Press: Example of The Guardian and Hürriyet - Kasap, Fevzi; Dolunay, Ayhan; İneci, Özcan (Journal of History Culture and Art Research, 2019)
Abstract With the invention of writing around BC 3000 and the invention of the printing in 1450s, developments occurred in culture, art, science and communication fields and the human beings started to communicate and interact with each other. The immigration phenomenon, which can date back as far as the human history also developed and continued to increase with the globalization and the developments in communication tools. These two important facts developed and increased parallel with each other and they became the most important subjects of the world in recent times. The refugee and asylum-seeker movements form the world agenda nowadays and it continues to be in the agenda due to press and media organisations following the subject closely and creating a public opinion. The growing refugee crisis gained speed and continued to increase especially with the protests and civil wars called “The Arab Spring”, happening in the Arabic peninsula, and became the most emphasized topic by the media and the press agencies of many countries. In this study, six days’ news coverage on the topic of refugees in The Guardian in England and the Hürriyet newspaper in Turkey were analysed and compared. The study will try to explain and focus on the similarities and differences between these news contents, from what perspective the refugee problems are looked at and how they are reported in the news. Öz M.Ö 3000’li yıllarda yazının bulunması ve 1450’li yıllarda matbaanın bulunmasıyla kültür, sanat, bilim ve iletişim alanında gelişmeler meydana gelmiş, insanlar birbirleriyle iletişim ve etkileşime geçmeye başlamışlardır. İnsanlık tarihi kadar eski olan göç olgusu da aynı şekilde küreselleşme ve iletişim araçlarına koşut olarak gelişim göstermiştir. Bahse konu olgular, günümüz dünyasında, yüksek önemi haiz yapıdadır. Bu çeçervede, mülteci ve sığınmacı hareketleri, basın yayın kuruluşlarının konuyu yakından takip edip kamuoyu oluşturmalarıyla, dünya gündeminde yer bulmayı sürdürmektedir. Özellikle Arap yarımadasındaki “Arap Baharı” olarak adlandırılan, protesto ve iç savaşlarla hız kazanan ve artarak devam eden mülteci krizi birçok ülkenin basın yayın kuruluşları tarafından önemle üzerinde durulan bir konu haline gelmiştir. Bu çalışmada İngiltere’deki The Guardian ve Türkiye’deki Hürriyet gazetelerinin mülteci konusu hakkında yapmış oldukları altı günlük haberleri incelenip karşılaştırılmıştır. Bu haberler arasındaki benzerlik ve farklılıklar üzerinde durularak haberlerde mülteci sorunlarına hangi açıdan bakıldığı ve değinildiği, haberlerin içerikleri incelenerek açıklanmaya çalışılacaktır.